SYNTHESIS OF OPTIMAL DIGITAL CONTROLLER FOR THE FIFTH ORDER CONTROLLED OBJECT - A. G. Stryzhniou; H. V. Lednik; A. N. Rusakovich (Informatika)
Synthesis of optimal digital controller for an electro-hydraulic system with the fifth order nonstatic controlled object containing oscillatory elements has been carried out. The system performance with such object and the designed optimal digital controller are verified via mathematical simulation. The achieved results are recommended to be used in practical implementation of similar digital automatic control systems.